Financial repression in general equilibrium: The case of the United States, 1948-1974 - Martin Kliem; Alexander Kriwoluzky; Gernot J. Müller; Alexander Scheer (Deutsche Bundesbank, 2024)
Financial repression lowers the return on government debt and contributes, all else equal, towards its liquidation. However, its full effect on the debt-to-GDP ratio hinges on how repression impacts the economy at large because it alters investment and saving decisions. We develop and estimate a New Keynesian model with financial repression. Based on U.S. data for the period 1948-1974, we find, consistent with earlier work, that repression was pervasive but gradually phased out. A model-based counterfactual shows that GDP would have been 5 percent lower, and the debt-to-GDP ratio 20 percentage points higher, had repression not been phased out.
Keywords: H63; E43; G28; 330; Financial repression; Government debt; Interest rates; Banks; Regulation; Bayesian estimation